Kadar Kalsium Dan Fosfor Pada Tulang Tikus Betina Yang Diberi Tepung Tempe Rendah Lemak (CALCIUM AND PHOSPHORUS LEVELS ON RAT BONE FEMALES GIVEN FAT-LOW TEMPE FLOUR) - Tangalayuk, Reggy Raisa; Suarsana, I Nyoman; Utama, Iwan Harjono (Buletin Veteriner Udayana, 2015)
Tempe contains of resources mineral that can be used to help bone formation during growth.This study aimed to determine the levels of calcium, phosphorus and calcium-phosphorus ratiotibia on female rats administered fat-low tempe flour. This study was used completely randomizeddesign (CRD) consisted of five treatment groups, each consisted of three rats. This study was usedof 25 female rats Spraque Dawley strain age two months were divided into five treatment groupsi.e.,  K1: rat control normal treatment; K2 - K5: normal rats given fat-low tempe flour doses of 1, 2, 4, and 6 mg/200g bb/day repectively, orally.  At the end of treatment the rats were sacrificed byanesthesia. Tibia bones were taken for analysis of the calcium and phosphorus levels using AASmethod (atomic absorbance spectrophotometer) and spectrophotometry method. The resultsshowed calcium levels in rats treated with low-fat soybean flour tends to increase with increasingdose when compared to control although not significantly different. Phosphorus levels was tend toincrease with increasing dose and significantly different. In contrast, the ratio of calcium andphosphorus tibia decreased with increasing dose of fat-low tempe flour but not significantly different.
Keywords: calcium; phosphor; bone; tempe; rat